Smart Contracts, Cryptocurrencies, and Donation Systems: A Bibliometric Analysis of Blockchain in Charity - Nur Aqilah Hazirah Binti Mohd Anim; Norfhadzilahwati Rahim; Nur Ilyana Ismarau Tajuddin; Azuan Ahmad; Anita Ismail (UNISEL PRESS, 2026)
Indexed by MyCite